GE_GERICHTE P/12273/2018 vom 8. Mai 2019 - GE Cour de justice (2019)
ERREUR DE DROIT(DROIT PÉNAL) ; DISPOSITIONS PÉNALES DE LA LEI ; ACTIVITÉ LUCRATIVE IRRÉGULIÈRE | LEI.115; LEI.41; OASA.71a; OASA.31